1982
DOI: 10.1111/j.1440-0960.1982.tb00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Hirsutism: Correlation of Severity of Hirsutism With Degree of Hyperandrogenism

Abstract: correlate ihe severity offnrsulism (as tiraded hv ihe metfiod ofFerrini appeared lo be a belter itulex of tfie h\percindro^eiut state that] t}ieas degree of hyperandrogenism correlates with (4) Sample

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1987
1987

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Most studies to date have demonstrated ele vations in free or non-SHBG-bound T in IH when total T is normal because the binding capacity of SHBG is lowered. [21][22][23][24][25] Although it has been suggested that virtually all hirsute women may have an increase in free T, 21 there are clearly some women in whom such an abnormality cannot be detected. Furthermore, al though elevated, plasma free T does not correlate with the severity of hirsutism in women, leaving part of the puzzle unexplained.…”
Section: Abnormal Androgen Production In "Idiopathic" Hirsutismmentioning
confidence: 99%
“…Most studies to date have demonstrated ele vations in free or non-SHBG-bound T in IH when total T is normal because the binding capacity of SHBG is lowered. [21][22][23][24][25] Although it has been suggested that virtually all hirsute women may have an increase in free T, 21 there are clearly some women in whom such an abnormality cannot be detected. Furthermore, al though elevated, plasma free T does not correlate with the severity of hirsutism in women, leaving part of the puzzle unexplained.…”
Section: Abnormal Androgen Production In "Idiopathic" Hirsutismmentioning
confidence: 99%